Tiruppavai of Goda : our lady saint Andral's Krishna poem - Simha, S. L. N. (Ananthacharya Indological Research Institute series ;, 1982)
Exposition of Āṇṭāḷ's Tiruppavai, classical Tamil poem in praise of Krishna, Hindu deity.